If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3y+5.2=2-4y
We move all terms to the left:
3y+5.2-(2-4y)=0
We add all the numbers together, and all the variables
3y-(-4y+2)+5.2=0
We get rid of parentheses
3y+4y-2+5.2=0
We add all the numbers together, and all the variables
7y+3.2=0
We move all terms containing y to the left, all other terms to the right
7y=-3.2
y=-3.2/7
y=-2.66666666667/5.83333333333
| 5x-3(x-2)=-9+5x-3 | | 5=z−4−35=(z/−4)−3. | | 2/3=4/5x | | 2/3x-5/6=1/4+1/2x | | -16.81=x-4.83 | | 16=3x-17 | | 2x+14=x=8 | | 4^x-5.2^x+4=0 | | -34y=-6 | | 2x-15=x-11 | | x3-2=7 | | 3(3x-3)=3 | | -16=4y+12 | | 14=4y-14 | | 18=-5(6n+6) | | 11.14=x-799 | | 3/5x-11=43 | | -17+24i=-31 | | 2x+4x-14=4- | | 6(u+6)-8u=32 | | -31+7k=6(k-6) | | 8x-6x-20=10 | | 4x/20=x-3/2 | | 15r-18=14r-10 | | 47=2v+11 | | s÷4=6 | | x+18.01=2.68 | | 2/3y+8=26 | | -11p+13=-2p-17p-19 | | |3m|=12 | | 6j+8=2j-16 | | 20-5u+20=7u-20 |